Board Diversity and Its Impact on Corporate Performance of Public Companies Listed in Amman Stock Exchange: The Case of Banks and Insurance Companies - khadash, Husam; Washali, Abdulrahman (Jordan Journal of Business Administration, 2019)
Board of directors has an important role in leading success of companies' performance. The board has very distinct functions and responsibilities within the organization. Basically, it is the role of the board of directors to hire the CEO or general manager of the business and evaluate the overall direction and strategy. Boards have major tasks, as stated in different regulations, such as responsibilities of top management and its performance assessment, its strategic objectives and risk management, in addition to organizing the relation with different stakeholders. Recently, there have been considerable discussions among academic researchers about differences and diversity of the board of directors, which gained a wide range of interest through studies conducted and points of views given because of their impact on firm performance. The current study aims at examining the impact of board diversity on the financial performance through investigating all banks and insurance companies listed in Amman Stock Exchange. These included 15 banks and 23 insurance companies for the financial period (2010-2015). Descriptive results revealed a poor representation of females and PhD holders as members in the board of directors compared to an acceptable representation of other members who are foreigners and master degree holders. In contrast, boards of directors show a high representation of non-executive members. In the same context and based on (LM) test for selecting between (OLS) model and random model effects (RMEs), the study concluded that there is no impact of gender, nationality and educational diversity on return on assets (ROA) or on return on equity (ROE).